The concept of a system for monitoring the investment activity of natural monopolies - N. E. Kotova; N. V. Kuznetsov (Управление)
The construction of a monitoring system for investment activities of natural monopolies is considered. It is noted that the companies of this type play a key role in regional development and consequently their investment strategy should be linked with the strategies of the country’s spatial and economic development. It is shown that in spite of the developed theoretical base in the field of project management, in practice, there are often failures in the timing of project implementation, a violation of financial discipline, inefficient resource management, etc. A significant number of investment projects is failed - either they do not reach the established performance targets or are not finished. The approach to the formation of investment plans of subjects of natural monopolies covering four aspects is presented: the time (project’s calendar plan), the cost (project’s budget), the risk (risk-analysis of the project), and key performance indicators (expected interim and final indicators of the project). The features of the formation and calculation of a system of indicators in these areas are considered. An example of calculating the need for project financing taking into account the necessary reserves is given. The concept of building a monitoring system for the implementation of long-term investment projects of natural monopolies is proposed, aimed at identifying deviations from the original plan at the earliest stages of their occurrence. The monitoring methodology is based on control the compliance of the actual schedule of work performed with the approved calendar plan, actually incurred and planned costs, actual and planned risks, and actually achieved and expected performance indicators of the project. The proposed approach allows to sequentially and orderly control the process of project execution control, and to ensure timely and reliable accounting of investment indicators in federal and regional economic policies and strategies.